Pollen morphology and their viability of some Indian mangroves - Gupta, Suparna; Ghosh, Arunima; Maity, Subrata; Das, Sauren (Annals of Tropical Research, 2008)
A study on pollen morphology of four common Indian mangroves from Sundarbans mangrove swamps, three species from the family Rhizophoraceae (Bruguiera sexangular Laur., Ceriops tagal Perr. and Rhizophora mucronate Lamk.) and one species from the family Avicenniaceae (Avicennia marina Forsk.) was carried out. Shape of the pollen grains were prolate, prolate spheroidal and subprolate with tricolporate apertures. Surface ornamentation of the studied taxa was reticulate, finely or scabrate. Pollen grain viability of the said taxa was determined by stain test (1% aceto-orcein) under in situ condition and percentage of viable pollen production was recorded. The result revealed that all the studied taxa produce a fairly good amount of viable pollen grains in natural condition, an indication that they are good propagule producer in the long run. Pollen grain germination and measurements of pollen tube length using different sucrose concentrations (0.2, 0.6, 1.0, 1.2, 1.6 and 2.0%). Maximum pollen fertility and pollen tube length occurred in 2% sucrose solution in case of A. marina and B. sexangular, whereas 1.6% in C. tagal and 1.0% in R. mucronata. A strong positive correlation exist between pollen germination and pollen tube length, but there was a hardly relation between sucrose concentration and pollen tube length.